National spiritual heritage is the source of our spirituality - KhudayberdiyevKh.Kh (Genius Journals, 2024)
The articie considers the cultural inheritance of the spiritual heritage, the concept of national heritage, the personality of each nation, their attitudes towards inheritance, the differences in attitude towards inheritance, the ancient and richness of the spiritual heritage of the Uzbek people, the ancient and richness of the spiritual heritage of oun people, studying, contributing to the sphere, collecting of written literature, manuscripts, jubilee of great thenkers, their works and the analysis of the development of the spiritual heritage of our people
Keywords: cultural heritage; spiritual heritage; national spiritual heritage